Cost‐effectiveness of professional‐mode flash glucose monitoring in general practice among adults with type 2 diabetes: Evidence from the GP‐OSMOTIC trial. Issue 3 (27th November 2021) - Hua, Xinyang; Catchpool, Max; Clarke, Philip; Blackberry, Irene; Chiang, Jason; Holmes‐Truscott, Elizabeth; Jenkins, Alicia; Khunti, Kamlesh; O'Neal, David; Speight, Jane; Furler, John; Manski‐Nankervis, Jo‐Anne; et al.
Abstract: Aim: To assess the cost‐effectiveness of professional‐mode flash glucose monitoring in adults with type 2 diabetes in general practice compared with usual clinical care. Methods: An economic evaluation was conducted as a component of the GP‐OSMOTIC trial, a pragmatic multicentre 12‐month randomised controlled trial enrolling 299 adults with type 2 diabetes in Victoria, Australia. The economic evaluation was conducted from an Australian healthcare sector perspective with a lifetime horizon. Health‐related quality of life (EQ‐5D) and total healthcare costs were compared between the intervention and the usual care group within the trial period. The 'UKPDS Outcomes Model 2' was used to simulate post‐trial lifetime costs, life expectancy and quality‐adjusted life years (QALYs). Results: No significant difference in health‐related quality of life and costs was found between the two groups within the trial period. Professional‐mode flash glucose monitoring yielded greater QALYs (0.03 [95% CI: 0.02, 0.04]) and a higher cost (A3807 [95% CI: 3604, 4007]) compared with usual clinical care using a lifetime horizon under the trial‐based monitoring frequency, considered not cost‐effective (incremental cost‐effectiveness ratio = A120, 228). The intervention becomes cost‐effective if sensor price is reduced to lower than 50%, or monitoring frequency is decreased to once per year while maintaining the same treatment effect on HbA1c . Conclusions: Including professional‐mode flash glucose monitoring every 3 months as part of a management plan for people with type 2 diabetes in general practice is not cost‐effective, but could be if the sensor price or monitoring frequency can be reduced.